2021
DOI: 10.4235/agmr.21.0051
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Experiences and Adaptation Strategies during the Midst of COVID-19 Crisis: A Qualitative Instrumental Case Study

Abstract: Because of their social vulnerabilities, older persons are among the most affected special population during the coronavirus disease 2019 (COVID-19) pandemic. 1) Moreover, this population has higher risks of acquiring such illnesses owing to their advanced age and the presence of chronic comorbidities. 2) In the Philippines, there were 1,276,004 confirmed cases of COVID-19, with 21,969 deaths, with a high mortality rate disproportionately affecting older Filipinos. 3) This health crisis has a notable dispropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…Different studies have reported that the elderly are actually more resilient to anxiety, depression, and stress-related mental health disorders [ 54 ]. Alodhayani et al [ 49 ] highlighted that increasing age appears to confer protection against distress, despite being the most vulnerable group to SARS-CoV-2 infection, probably because of the development of more efficient psychological coping and adaptability during COVID-19 [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported that the elderly are actually more resilient to anxiety, depression, and stress-related mental health disorders [ 54 ]. Alodhayani et al [ 49 ] highlighted that increasing age appears to confer protection against distress, despite being the most vulnerable group to SARS-CoV-2 infection, probably because of the development of more efficient psychological coping and adaptability during COVID-19 [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being the most vulnerable group to SARS-CoV-2 infection and COVID-19 mortality, older adults as a subpopulation have been observed to be much more resilient to the anxiety, depression, and stress-related mental health disorders compared to their younger counterparts in the ongoing COVID-19 pandemic [38]. Older adults tend to be more internally resilient, which means they have developed a sense of internal control to adapt to changes brought about by external threats and perceived crisis, better known as the need-threat internal resiliency theory [39]. Another explanation is the adaptive coping of older adults, who tend to be more positive [40].…”
Section: Discussionmentioning
confidence: 99%
“… 9 ) Moreover, accessing fundamental health information, obtaining a genuine understanding of the principles of disease prevention, and managing public health remained crucial, especially for at-risk populations. 10 , 11 ) Making decisions about how to follow health advice was one of the processes necessary for COVID-19 prevention behaviors. 12 )…”
Section: Introductionmentioning
confidence: 99%